TC4钛合金板抗高强杆弹正撞击侵彻特性实验研究 - 杨永刚; 冯岩; 魏刚; 邓云飞 (Jixie qiangdu)
The test of rod impact on TC4 titanium alloy plate with a thickness of 10 mm was carried out on a light gas gun,in order to study the damage behavior and the effect of projectile head shape on the anti-penetration performance of the target plate.The ballistic limit velocities of target plates were obtained under various impact conditions.The damage characteristics and mechanism of target plate were analyzed by microscopic observation.The results show that the failure modes of TC4 plates are different when impacted by blunt-nose projectile and ogival-nose projectiles,and the anti-penetration capability of target to ogivalnose projectile is better than that of bunt-nose projectile.After impacted by ogival-nose projectile,the front perforated and the back peeled off of targets were observed,as well as the shape of the back perforation is approximately conical.However,the damage of the target plate is shear plug type,accompanied by the neat edge and smooth inner wall of the impact hole.In addition,the adiabatic shear bands were observed by scanning electron microscope when the blunt-nosed projectile penetrated the target plate.